2022
DOI: 10.3390/life12111925
|View full text |Cite
|
Sign up to set email alerts
|

Network Pharmacology and Experimental Validation to Investigate the Antidepressant Potential of Atractylodes lancea (Thunb.) DC.

Abstract: Atractylodes lancea (Thunb.) DC. (AL) has been indicated in traditional prescriptions for the treatment of depression. However, the mechanism of action of AL in the treatment of depression is still unclear. This study aimed to investigate the antidepressant potential of AL using network pharmacology, molecular docking, and animal experiments. The active components of AL were retrieved from the traditional Chinese medicine systems pharmacology database and analysis platform (TCMSP), and the depression-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Neurotransmitter receptors are chief components of the neuroactive ligand–receptor interaction pathway, which plays a pivotal role in the pathophysiology of several brain disorders. The role of the calcium signaling pathway has also been implicated in different mental conditions, and the disruption of the Ca 2+ -CaM-NO/sGC (calcium-calmodulin-nitric oxide-activated guanylyl cyclase pathway) signaling cascade could result in the neuroprotective effects [ 141 ]. In this way, CLAE may exert its anxiolytic, antidepressant and memory-enhancing effect by targeting multiple underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotransmitter receptors are chief components of the neuroactive ligand–receptor interaction pathway, which plays a pivotal role in the pathophysiology of several brain disorders. The role of the calcium signaling pathway has also been implicated in different mental conditions, and the disruption of the Ca 2+ -CaM-NO/sGC (calcium-calmodulin-nitric oxide-activated guanylyl cyclase pathway) signaling cascade could result in the neuroprotective effects [ 141 ]. In this way, CLAE may exert its anxiolytic, antidepressant and memory-enhancing effect by targeting multiple underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular components (CC), molecular functions, biological processes, and pathways were all screened for target genes. KEGG pathway bubble charts made with SRPLOT (http://bioinformatics.com.cn/, accessed on 3 December 2022) were of particular interest [17].…”
Section: Target Protein Gene Ontology and Kegg Enrichment Analysismentioning
confidence: 99%
“…The stronger the association between the proteins corresponding in the network, the higher the degree in the network interaction, indicating th proteins play a vital part and are deemed to be the hub genes. Based on degre ten topmost hub genes were screened, including MAPK3 (22), TNF (20), IL (19), PPARG (18), MAPK1 (17), CNR1 (13), MTOR (13), NR3C1 (11), and IGF1 The overlapped proteins were uploaded to STRING version 11.5, and high-certainty interacting proteins data with a score >0.7 were accepted for the PPI network development (Figure 3). The stronger the association between the proteins corresponding to the node in the network, the higher the degree in the network interaction, indicating that the target proteins play a vital part and are deemed to be the hub genes.…”
Section: Network Pharmacology Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In general, network pharmacology utilizes the systems biology methods to analyze biological networks (e.g., metabolic or signaling pathways, protein-protein interactions) in order to infer drug actions and interactions with various targets [199]. Multiple recent studies have revealed drug targets of phytocomponents from extracts with antidepressant effects [193,194,[200][201][202], and a similar approach has been used to search for drug targets related to the treatment of schizophrenia by known schizophrenia drugs [203]. Some studies also combine docking with (Q)SAR methods, e.g., identifying monoamine neurotransmitters reuptake inhibitors as antidepressants [204] or a selective positive allosteric modulation of α1containing GABA-A receptors [196].…”
Section: In Silico-driven Search For Novel Therapeutic Agentsmentioning
confidence: 99%